Meta Analysis: Risk Factor Analysis of Dengue Disease Incidence in Indonesia - Keman, Soedjajadi; Azizah, R; Hamzah, Firdaus Mohamad (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: Dengue fever is endemic in over 100 countries, Africa, America, and several other European countries. Indonesia became the top of the list a few years ago. The study aimed to analyze risk factors (hanging clothes, water reservoir conditions, and jumantik cadres) with the incidence of DHF. Methods: This is quantitative research with meta-analysis. Meta-analysis has four stages: data abstraction, data analysis using JASP Version 0.18.3, and publication bias test. Conduct heterogeneity tests, funnel plots, egger tests, and forest plots. Results and Discussion: The heterogeneity test of hanging clothes and water reservoirs using a random effects model because p-value smaller than 0.05. Jumantik cadre using the fixed effects model is larger than p < 0.001 i.e. p = 0.303. The forest plot of hanging clothes has pooled value PR=e0.26 = 1.297 (95% CI -0.05-0.57), pooled water reservoir value PR= e0.55 = 1.73 (95% CI 0.30 - 0.79), and jumantik cadre pooled value OR= e0.70= 2.01 (95% CI 0.24 - 1.33). The highest risk factor for dengue cases is jumantik cadres with the pooled value obtained PR = e0.70 = 2.01 (95% CI 0.24 – 1.33). Conclusion: Based on the results of the meta-analysis in this study, jumantik cadres has the greatest risk factor value compared to other variables. The second highest risk factor was in water reservoirs, followed by the next variable hanging clothes.